The application of randomization test of hypothesized order relation for validation of the structure of Holland‘ s hexagonal model in structure of Isfahan university student‘s vocational interests. - M. Akbarzadeh; Mohamadreza Abedi; I. Baghban (رویکردهای نوین آموزشی, 2010)
The purpose of this research was to introduce the application of randomization test of hypothesized order relation for validation the models that are based on hypothetical order pattern of relation between factors. As an example of application of this procedure, the holland‘s hexagonal model of vocational interest was selected and its validity in comparison with the structure of vocational interests of students (n=300)of Isfahan university was examined .similar to many other cross cultural studies, results showed good fitness for holland‘s riasec model in describing the structure of Isfahan university students‘ vocational interests (ci=0.71;p=0.02).the results support the structural validity of OP-PGI in an Iranian context .applications, advantages ,and limitations of this Ptocedure and some suggestions were discussed.